(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current study aimed to investigate the reality of e-learning and the obstacles to its implementation in Libyan higher education institutions from the perspective of faculty members at university of Tripoli, Libya. The study relied on a descriptive analytical approach, applying it to a sample of 235 participants from the total study population, which includes all faculty members at the university in applied disciplines. To achieve the study objectives, an electronic questionnaire was developed consisting of 41 items distributed over five axes: obstacles related to the educational environment, the teacher, the student, the educational material, and distance learning. Statistical analysis of the questionnaire was conducted using Pearson’s correlation coefficient to verify the validity of the research tool, Cronbach’s alpha to measure the stability of the tool, as well as means, standard deviations, and relative weights to identify the most prominent obstacles to the implementation of e-learning in higher education. In addition, an independent samples t-test was used to determine whether there were differences in the level of e-learning implementation obstacles based on gender variable, while a one-way analysis of variance was used to assess whether there were differences based on years of teaching experience in higher education. The most important results of the study are as follows: Obstacles related to the educational environment ranked first with a very high score of an arithmetic mean of 4.44, followed by obstacles related to the student with a high score, with an arithmetic mean of 3.83, and then obstacles related to distance learning with a high score, of an arithmetic mean of 3.74. The obstacles related to the teacher came in fourth place with a high degree, with an arithmetic mean of (3.67), then the obstacles related to the educational material came in last place with a high degree, with an arithmetic mean of (3.61). The study also showed that there was no statistically significant difference in the average responses of the research samples regarding the most prominent obstacles to employing virtual education in teaching applied sciences attributed to the gender variable. Meanwhile there were statistically significant differences observed in the first three research axes (the educational environment, the teacher and the student), as well as the total score of the questionnaire, attributed to the experience variable. Based on these results, the study came out with many recommendations and proposals that focus on the need to work to address the obstacles revealed by the current study, provide an appropriate educational environment, and hold awareness and educational courses for all members of the educational process; to optimally benefit from virtual laboratories. It is also necessary to emphasize the need to activate the system of integrating e-learning with traditional education and consider it an approved educational model to ensure the continuity of the educational process in all conditions of the country.